2019
DOI: 10.1108/jkm-12-2018-0738
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge management and social entrepreneurship education: lessons learned from an exploratory two-country study

Abstract: Purpose Social entrepreneurship courses are among the fastest growing category of course offerings to entrepreneurship students (Brock and Kim, 2011) because both high growth potential- and steady growth-social ventures can create value and help solve social issues effectively and efficiently. As knowledge disseminators, entrepreneurship educators are in prime position to develop the knowledge, skills and abilities of students, which, in turn, increases their intentions to start a social venture and their abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 67 publications
1
22
0
5
Order By: Relevance
“…Of course, some papers do not explicitly focus on how to attract, capture, retain, stock, share – in other words – or manage knowledge in entrepreneurship but we simply note that the literature on the role of knowledge during the creation process of the business remains highly prolific. More importantly, and as mentioned in the introduction of this paper, entrepreneurship is found in many different situations under different contexts, and therefore, we agree with Malsch and Guieu (2019), who claim that social entrepreneurship differs from other forms of entrepreneurship and with Solomon et al (2019), who note that students seek courses in social entrepreneurship and not entrepreneurship per se . Despite this strong difference between social entrepreneurship and other forms of entrepreneurship, we claim there might be a need to expand this SLR by integrating “knowledge management” and “entrepreneurship”, and therefore, showing in a more precise manner how KM practices differ in both approaches.…”
Section: Conclusion and Future Research Directionssupporting
confidence: 85%
See 1 more Smart Citation
“…Of course, some papers do not explicitly focus on how to attract, capture, retain, stock, share – in other words – or manage knowledge in entrepreneurship but we simply note that the literature on the role of knowledge during the creation process of the business remains highly prolific. More importantly, and as mentioned in the introduction of this paper, entrepreneurship is found in many different situations under different contexts, and therefore, we agree with Malsch and Guieu (2019), who claim that social entrepreneurship differs from other forms of entrepreneurship and with Solomon et al (2019), who note that students seek courses in social entrepreneurship and not entrepreneurship per se . Despite this strong difference between social entrepreneurship and other forms of entrepreneurship, we claim there might be a need to expand this SLR by integrating “knowledge management” and “entrepreneurship”, and therefore, showing in a more precise manner how KM practices differ in both approaches.…”
Section: Conclusion and Future Research Directionssupporting
confidence: 85%
“…Further, in the field of social entrepreneurship, it has been shown by Campos-Climent and Sanchis-Palacio (2017) that the capacity for knowledge absorption positively impacts the creation of shared value in social enterprises in the euro-Mediterranean region. Through the analysis of North American social entrepreneurship education programmes, Solomon et al (2019) highlighted the potential of the knowledge management field and courses in social entrepreneurship education, which present a continuously high demand in the US and Canada, where it continues to rise.…”
Section: Findings From the Literature Reviewmentioning
confidence: 99%
“…Desde luego, Thompson, Alvy, & Lees (2000) ya abordaban una descripción critica respecto a la creación de capital social generada por emprendedores sociales, describiéndolos como líderes que identifican necesidades sociales en contextos específicos y generan los recursos para cubrirlas, del mismo modo, resaltan la relevancia del deseo interno que experimentan los emprendedores por ayudar. Recientemente los estudios en emprendimiento social ya se abordan dentro del campo de la educación, por ejemplo, Hamizan-Roslan, Hamid, Taha Ijab, & Bukhari (2019) contribuyen con datos relevantes para integrar la formación en emprendimiento social en la educación superior; del mismo modo Solomon, Alabduljader, & Ramani (2019) exponen el crecimiento en la demanda de formación en emprendimiento social por parte de estudiantes universitarios y abordan algunas tendencias respecto a la educación en emprendimiento social.…”
Section: Introductionunclassified
“…Ashcraft et al (2019) discussed the ownership and definition of social entrepreneurship curriculums in the early stage, and put forward three development paths of social entrepreneurship curriculum: social entrepreneurship curriculums under business schools, non-profit enterprise curriculums, and mixed social entrepreneurship curriculums. Later, based on the results of cross research, compared with the opening and enrollment of business entrepreneurship education courses in the same period, Solomon et al (2019) concluded that nowadays college students have strong social entrepreneurship tendencies and a strong demand for their development status. In contrast, the supply of social entrepreneurship courses is insufficient.…”
Section: Literature Reviewmentioning
confidence: 99%